International Experience of Community Participation in the School Education Management - Yu. V. Belousov; O. I. Timofeeva (Управленческие науки)
Community participation in management helps to improve the quality of planning of educational work in order to meet people’s needs better and allows the organization of efficient monitoring of the quality of knowledge and skills of school students by consumers. The purpose of this article is to study current modes of community participation in school education management abroad and to analyze their possible implementation in the Russian environment. Methodologically, the modes of community participation have been studied at all levels of education management: national, regional, and institutional. Different modes of community participation in the educational process management are regarded as an element of an integral system. Based on results of the conducted analysis it has been concluded that, to enhance the management system in general education in Russia, the use of certain foreign practices seems to be reasonable, provided that they are tailored to the Russian system. The methods of involvement of independent experts and organizations in the implementation of certain functions of the State in the field of school education are of interest. Moreover, there can be used various modes of community participation in the quality of education monitoring in schools. The implementation of such practice in the Russian system of school education management will help to enhance the quality of school education.